OBTENÇÃO DE NANOCOMPÓSITOS DE ÓXIDO DE GRAFENO/NANOTUBOS DE TITANATOS PARA A APLICAÇÃO EM FOTOCATÁLISE - KURAMORO, Mariana Yumi Simões; DIAS, Fabricia E. M.; SAMPAIO, Julia Bortolusso; PESSOA, Kauane Kashyiama; SILVA, Thais; RODRIGUES, Daniela Cristina Manfroi (ANAIS DO ENIC, 2020)
-